Utilization of ICT in Improving Four Arabic Language Learning Skills in Higher Education - Nuraini, Rini; Guilin, Xie; Jiao, Deng; Sarip, Mohamad; Mahfuz, Taufik Warman (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The use of ICT is everything that is used to communicate and create, manage and distribute information. The use of ICT can help Arabic language students in improving the four maharah skills. By applying ICT in learning, students' difficulties in the Arabic learning process can be significantly reduced. This is due to the innovation in learning in higher education by utilizing ICT during the teaching and learning process of students. The purpose of this research is to support Arabic language learning with ICT learning system in higher education. The method used in this research is quantitative method, which can show that this research contains numerical data. The data was obtained by using geogle from as a means to create a questionnaire containing questions and then distributed to respondents who were used as research subjects. The results showed that with the utilization of ICT in learning, it can improve four Arabic language skills in college. The conclusion of this study is that ICT can be used in learning Arabic to increase student enthusiasm and know the ability to understand Arabic learning in college. The limitation of this study is that the researcher only conducted research on the utilization of ICT as a medium of Arabic learning